Feasibility and efficacy of gemcitabine plus cisplatin combination therapy after curative resection for biliary tract cancer. (30th August 2015) - Kainuma, Osamu; Miura, Fumihiko; Furukawa, Daisuke; Yamamoto, Hiroshi; Cho, Akihiro; Sano, Keiji; Nakagohri, Toshio; Asano, Takehide
Abstract: Background: The aim of this multi‐institutional study was to assess the feasibility and the efficacy of gemcitabine plus cisplatin (CDDP) combination therapy (GC therapy) for biliary tract cancer (BTC) in the adjuvant setting. Methods: Eligible patients identified between January 2008 and January 2013 were enrolled. GC therapy at 1, 000 mg/m 2 of gemcitabine and 25 mg/m 2 of CDDP on days 1 and 8 repeated every 3 weeks was performed for 6 months. The primary endpoint was the feasibility and the adverse events, and the secondary endpoint was recurrence‐free survival (RFS) and overall survival (OS). Results: Among 29 evaluable patients, the protocol was completed in 21 (72%) patients. Relative dose intensity (RDI) of gemcitabine and CDDP was 77% and 81%, respectively. There was no difference in the completion rate and the RDI between patients who underwent resection with vs. without major hepatectomy. Grade 3–4 toxicities included leukopenia (14%) and neutropenia (27%). Two‐year RFS and 2‐year OS was 59% and 90%, respectively. Conclusions: Standard dose of GC therapy is tolerable in patients with BTC who underwent curative resection either with or without major hepatectomy. The survival effect of this regimen is promising, but further comparative study is needed. Abstract : Highlight In this multi‐institutional study, Kainuma and colleagues showed that standard‐dose gemcitabine plus cisplatin combination therapy in the adjuvant setting was feasible with promising survival in patients who had undergone curative resection for biliary tract cancer either with or without major hepatectomy. These results pave the way for further comparative studies.